(untitled) - Fasick, Adele M (Westport, Conn., 2008)
This edition is organized into four major content areas: planning services for children in the context of a community; managing the department, which includes recruiting and retaining staff, communicating with colleagues, annual reports, budgeting, and security; managing services—including collection development, electronic resources, intellectual freedom, and outreach; and professional development. All of the sections have been updated to include new and relevant information especially in relation to technological advances and challenges
Keywords: Children’s libraries,Public libraries,Thư viện trẻ em,Thư viện công cộng; Administration,Administration,Quản trị,Quản trị; United States,United States,Hoa Kỳ,Hoa Kỳ